The Role of Parental Monitoring on Problematic Internet Use Among Adolescents - İlkay DEMIR (Muhammed Yıldız, 2017)
Present study aimed to examine the relative role of time spent on the internet, parents’ educational background and parental mobile phone and computer monitoring behaviors on problematic internet use among adolescents. Participants of the study were 250 high school students from İstanbul aged between 14 and 18. Problematic Internet Usage scale, Parental Monitoring Scale and Demografic Information Form were used to collect data. Results of the hierarchical regression analysis revealed that time spent on the internet, fathers’ education and parental computer monitoring together accounted for the 16% of the variance in problematic internat use among adolescents. While mothers’ educational background and parental mobile phone monitoring had no significant contribution in the model, time spent on the internet and fathers’ education were found to be stronger predictors of problematic internet use than parental computer monitoring.